Spontaneous transient hyperpolarizations in the rabbit small intestine - Kito, Yoshihiko (J Physiol, 2014)
Four types of electrical activity were recorded and related to cell structure by intracellular recording and dye injection into impaled cells in muscles of rabbit small intestine. The specific cell types from which recordings were made were longitudinal smooth muscle cells (LSMCs), circular smooth muscle cells (CSMCs), interstitial cells of Cajal distributed in the myenteric region (ICC-MY) and fibroblast-like cells (FLCs). Slow waves (slow waves(SMC)) were recorded from LSMCs and CSMCs. Slow waves (slow waves(ICC)) were of greatest amplitude (>50 mV) and highest maximum rate of rise (>10 V s(−1)) in ICC-MY. The dominant activity in FLCs was spontaneous transient hyperpolarizations (STHs), with maximum amplitudes above 30 mV. STHs were often superimposed upon small amplitude slow waves (slow waves(FLC)). STHs displayed a cyclical pattern of discharge irrespective of background slow wave activity. STHs were inhibited by MRS2500 (3 μm), a P2Y1 antagonist, and abolished by apamin (0.3 μm), a blocker of small conductance Ca(2+)-activated K(+) channels. Small amplitude STHs (<15 mV) were detected in smooth muscle layers, whereas STHs were not resolved in cells identified as ICC-MY. Electrical field stimulation evoked purinergic inhibitory junction potentials (IJPs) in CSMCs. Purinergic IJPs were not recorded from ICC-MY. These results suggest that FLCs may regulate smooth muscle excitability in the rabbit small intestine via generation of rhythmic apamin-sensitive STHs. Stimulation of P2Y1 receptors modulates the amplitudes of STHs. Our results also suggest that purinergic inhibitory motor neurons regulate the motility of the rabbit small intestine by causing IJPs in FLCs that conduct to CSMCs.